Financial shenanigans : how to detect accounting gimmicks and fraud in financial reports - Schilit, Howard Mark, 1952-; Perler, Jeremy; Engelhart, Yoni (McGraw Hill-Ascent Audio, 2018)
The bestselling classic from the "Sherlock Holmes of Accounting"--Updated to reflect the key case studies and most important lessons from the past quarter century. This fourth edition of the classic guide shines a light on the most shocking frauds and financial reporting offenders of the last twenty-five years, and gives investors the tools they need to detect: *Corporate cultures that incentivize dishonest practices*The latest tricks companies use to exaggerate revenue and earnings*Techniques devised by management to manipulate cash flow as easily as earnings*Companies that use misleading metrics to fool investors about their financial performance*How companies use acquisitions to hide deterioration in their underlying business This new edition focuses on the key case studies and most important lessons from the past quarter century, and brings you up to date on accounting chicanery in the global markets. Howard Schilit and his team of renowned forensic accounting experts expose financial reporting miscreants and unveil the latest methods companies use to mislead investors. You'll learn everything you need to know to unearth deceptive reporting and avoid costly mistakes